Bis-Retinoid A2E Induces an Increase of Basic Fibroblast Growth Factor via Inhibition of Extracellular Signal-Regulated Kinases 1/2 Pathway in Retinal Pigment Epithelium Cells and Facilitates Phagocytosis - Balmer, Delphine; Bapst-Wicht, Linda; Pyakurel, Aswin; Emery, Martine; Nanchen, Natacha; Bochet, Christian G.; Roduit, Raphael (Frontiers in Aging Neuroscience, 2017)
Age-related macular degeneration (ARMD) is the leading cause of vision loss in developed countries. Hallmarks of the disease are well known; indeed, this pathology is characterized by lipofuscin accumulation, is principally composed of lipid-containing residues of lysosomal digestion. The N-retinyl-N-retinylidene ethanolamine (A2E) retinoid which is thought to be a cytotoxic component for RPE is the best-characterized component of lipofuscin so far. Even if no direct correlation between A2E spatial distribution and lipofuscin fluorescence has been established in aged human RPE, modified forms or metabolites of A2E could be involved in ARMD pathology. Mitogen-activated protein kinase (MAPK) pathways have been involved in many pathologies, but not in ARMD. Therefore, we wanted to analyze the effects of A2E on MAPKs in polarized ARPE19 and isolated mouse RPE cells. We showed that long-term exposure of polarized ARPE19 cells to low A2E dose induces a strong decrease of the extracellular signal-regulated kinases’ (ERK1/2) activity. In addition, we showed that A2E, via ERK1/2 decrease, induces a significant decrease of the retinal pigment epithelium-specific protein 65kDa (RPE65) expression in ARPE19 cells and isolated mouse RPE. In the meantime, we showed that the decrease of ERK1/2 activity mediates an increase of basic fibroblast growth factor (bFGF) mRNA expression and secretion that induces an increase in phagocytosis via a paracrine effect. We suggest that the accumulation of deposits coming from outer segments (OS) could be explained by both an increase of bFGF-induced phagocytosis and by the decrease of clearance by A2E. The bFGF angiogenic protein may therefore be an attractive target to treat ARMD.